Sacrococcygeal teratoma associated with hindgut duplication: A case report & review of literature - Sandesh V. Parelkar; Beejal V. Sanghvi; Neha Sisodiya; Shalil H. Patil; Satej S. Mhaskar; Sanjay N. Oak (Elsevier, 2014)
The index case report describes a previously unreported coexistence of sacrococcygeal teratoma and a tubular duplication of the rectum. The child presented with a large sacrococcygeal mass. He was treated with pre-operative chemotherapy to reduce the bulk of the tumor and subsequently underwent surgical resection. Exploration surprisingly revealed an additional long tubular duplication of the rectum, which did not share any lumen with the parent gut. The duplication cyst and the residual tumor were excised. The histopathology report confirmed residual mature teratoma and the duplication cyst. Relevant literature is reviewed.